Infection with chikungunya virus confers heterotypic cross-neutralizing antibodies and memory B-cells against other arthritogenic alphaviruses predominantly through the B domain of the E2 glycoprotein. - John M Powers; Zoe L Lyski; Whitney C Weber; Michael Denton; Magdalene M Streblow; Adam T Mayo; Nicole N Haese; Chad D Nix; Rachel Rodríguez-Santiago; Luisa I Alvarado; Vanessa Rivera-Amill; William B Messer; et al. (PLoS Neglected Tropical Diseases)
Infections with Chikungunya virus, a mosquito-borne alphavirus, cause an acute febrile syndrome often followed by chronic arthritis that persists for months to years post-infection. Neutralizing antibodies are the primary immune correlate of protection elicited by infection, and the major goal of vaccinations in development. Using convalescent blood samples collected from both endemic and non-endemic human subjects at multiple timepoints following suspected or confirmed chikungunya infection, we identified antibodies with broad neutralizing properties against other alphaviruses within the Semliki Forest complex. Cross-neutralization generally did not extend to the Venezuelan Equine Encephalitis virus (VEEV) complex, although some subjects had low levels of VEEV-neutralizing antibodies. This suggests that broadly neutralizing antibodies elicited following natural infection are largely complex restricted. In addition to serology, we also performed memory B-cell analysis, finding chikungunya-specific memory B-cells in all subjects in this study as remotely as 24 years post-infection. We functionally assessed the ability of memory B-cell derived antibodies to bind to chikungunya virus, and related Mayaro virus, as well as the highly conserved B domain of the E2 glycoprotein thought to contribute to cross-reactivity between related Old-World alphaviruses. To specifically assess the role of the E2 B domain in cross-neutralization, we depleted Mayaro and Chikungunya virus E2 B domain specific antibodies from convalescent sera, finding E2B depletion significantly decreases Mayaro virus specific cross-neutralizing antibody titers with no significant effect on chikungunya virus neutralization, indicating that the E2 B domain is a key target of cross-neutralizing and potentially cross-protective neutralizing antibodies.